2021
DOI: 10.3389/fmicb.2021.733668
|View full text |Cite
|
Sign up to set email alerts
|

Insight Into Whole Genome of Aeromonas veronii Isolated From Freshwater Fish by Resistome Analysis Reveal Extensively Antibiotic Resistant Traits

Abstract: Aeromonas veronii outbreaks in tilapia farming caused relatively high mortalities, and the bacteria was resistant to many kinds of antimicrobials used in Thailand aquaculture. According to the CLSI standard, the determination of antimicrobials efficacy has been limited to phenotypic analyses, and a genomics study is required. This research aimed to analyze the resistome of A. veronii isolated from diseased tilapia in Chainat, Nong Khai, and Uttaradit provinces in Thailand. A total of 12 isolates of A. veronii … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 59 publications
(83 reference statements)
4
11
0
Order By: Relevance
“…isolates, and a minor group related to A. jandaei and A. sobria (Figure 1). This is consistent with other studies that have implicated species other than A. hydrophila in MAS outbreaks, including A. veronii in channel catfish in Vietnam (Hoai et al, 2019) and carp in China (Ran et al, 2018), and A. veronii and A. jandaei in tilapia in Thailand (Dong et al, 2017;Sakulworakan et al, 2021). This present study relied on opportunistic sampling and a structured epidemiological approach is necessary to understand the relative contributions of A. hydrophila including vAh ST251, A. dhakensis and other Aeromonas species and strains to MAS outbreaks in striped catfish in Vietnam.…”
Section: Discussionsupporting
confidence: 91%
“…isolates, and a minor group related to A. jandaei and A. sobria (Figure 1). This is consistent with other studies that have implicated species other than A. hydrophila in MAS outbreaks, including A. veronii in channel catfish in Vietnam (Hoai et al, 2019) and carp in China (Ran et al, 2018), and A. veronii and A. jandaei in tilapia in Thailand (Dong et al, 2017;Sakulworakan et al, 2021). This present study relied on opportunistic sampling and a structured epidemiological approach is necessary to understand the relative contributions of A. hydrophila including vAh ST251, A. dhakensis and other Aeromonas species and strains to MAS outbreaks in striped catfish in Vietnam.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings revealed that more than 90% of Aeromonas strains showed resistance to β‐lactam antibiotics such as AMC and AMP. These results also agree with the previous studies reported by many researchers (Azzam‐Sayuti et al, 2021; Sakulworakan et al, 2021). Many Aeromonas strains isolated from diseased freshwater fish in the studied ponds exhibited high antibiotic resistance against AMC and AMP, indicating that chromosomal encode β‐lactam resistance genes frequently produced in Aeromonas isolates microbes in the studied aquatic environment (Saavedra et al, 2004; Soto‐Rodriguez et al, 2018).…”
Section: Discussionsupporting
confidence: 94%
“…The aquaculture policy in Thailand allows several types of antibiotic groups, including beta‐lactams, quinolones, tetracyclines, and sulfonamides (FCSTD, 2012). These antibiotics have also been used frequently for human treatments (Sakulworakan et al, 2021). Nonprudent use of antimicrobials in aquaculture will significantly impact the development of antimicrobial‐resistant bacteria, transfer resistance properties between bacteria, and reduce the effectiveness of drugs for aquatic and terrestrial animals as well as humans (Rhodes et al, 2000; Yano et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although the pangenome classified the 15 genomes into four groups based on species, the high similarity of AMR genes determined by phylogenetic analyses is suggestive that there is interspecies transmission of AMR genes among bacteria species isolated from different hosts. This is also indicative that these genes could be part of the conserved genome across the aeromonads being in line with previous observations that Aeromonads are intrinsically resistant to β-lactams (Baron et al, 2017;Kabwe et al, 2020;Sakulworakan et al, 2021).…”
Section: Discussionsupporting
confidence: 90%